Automatic Interpretation Of Magnetic Data Using Euler Deconvolution With Modified Algorithm - Usman, Nuraddeen (2018)
The conventional Euler deconvolution has five unknown parameters to be solve which are the location of source (x0, y0 and z0), the background field (B) and the structural index (N). Among these 5 unknowns, the structural index is to be manually selected by the user. The manual input of structural index into the Euler equation makes the technique to be subjective and semi-automated. The objectives of this research are, to automate Euler deconvolution equation and introduce a filter for discriminating reliable solution from the inversion output. It is also part of the objectives of this research, to assess the effect of inclination on the new technique and investigate the accuracy of the introduced algorithm.